Persepsi Petani Terhadap Pengembangan Usahatani Bawang Merah Guna Meningkatkan Pendapatan Masyarakat di Desa Liya Togo Kecamatan Wangi-Wangi Selatan Kabupaten Wakatobi - Sari, Findy; Bafadal, Azhar; Mansyur, Ahmad (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
Â Farming is a sector hoding strategic role in national development, even tough, farming sector generally faced on some problems, such capital restristiveness and limited land area which owned by the farmer. The relation with exists potential, Indonesia has a rich living nature resources, but the community income is still not enough to cover their daily needs. Therefore, one of the way to increase the income is through utilization of resources available even more the resorces which can be wreaked in their environment such the utilization of limited land area or verticulture. This research was in Liya Togo, Wangi-Wangi District of South Wakatobi Regency. The determination or selection of research area was done in purpose with consideration that Liya Togo is the produce ofÂ onion in Wakatobi an the existence of unused yard by the society that be used to make additional income. The population of this research is all farmer in Liya Togo district in total of 35 people. The determination of respondent or sample using census, the total of population is the same with the total of respondent. The result of the research shows that the perception of the farmer toawrd onion verticulture farming development dominant on agree category because they can utilize limited house yard to be income additional source for the community in Liya Togo,which in the first question 35 respondent chose to agree (100%), the question about 11 respondent chose to neutral (57,14%), in the third question 22 respondent chose agree (62,86%) and the fourth question about 17 respondent chose agree (49%). The average income of onion farming in Liya Togo is Rp 899.814 in one production cycle